Acetate chitosan with CaCO3 doping form tough hydrogel for hemostasis and wound healing. (21st September 2018) - Zhou, Yaping; Li, Hongyu; Liu, Jiwei; Xu, Yan; Wang, Yonglu; Ren, Hao; Li, Xueming
Abstract : In recent years, chitosan has been applied for wound management due to its properties of biocompatibility, biodegradability, antimicrobial activity, and low immunogenicity. But the poor water solubility in neutral pH limited its further application in clinical wound healing. To overcome this problem, acetate chitosan was developed and approved as commercial products for wound healing. However, the acidity of acetate chitosan was potentially allergenic, and the poor mechanical properties of its formed hydrogels also hindered the therapeutic efficacy in wound care. In this study, CaCO3 was simply doped into acetate chitosan to form the wound dressing. After absorbing water, the H + of acetate chitosan reacted with CaCO3 to release Ca 2+, resulting in acidity decreased. The production of Ca 2+ and residue of CaCO3 cross‐linked with chitosan to form a tough hydrogel by electrostatic interaction. The physical characteristics, swelling, mechanical testing, and blood clotting were evaluated. The results in vitro demonstrated that after doping CaCO3 into acetate chitosan, the mechanical properties and blood clotting of the formed hydrogel were increased. Then, the evaluation of hydrogels in vivo revealed that it can also accelerate the wound healing by promoting re‐epithelization and collagen deposition. This simple way by doping CaCO3 into acetate chitosan can increase wound healing, and it can also broad the application of acetate chitosan in clinical use.